Answer:
x = -0.6
y = 2.2
z = 2
Step-by-step explanation:
2x + y - 2z = -3
x + 3y - z = 4
3x + 4y - z = 5
Rewrite the system in matrix form and solve it by Gaussian Elimination (Gauss-Jordan elimination)
2 1 -2 -3
1 3 -1 4
3 4 -1 5
R1 / 2 → R1 (divide the 1 row by 2)
1 0.5 -1 -1.5
1 3 -1 4
3 4 -1 5
R2 - 1 R1 → R2 (multiply 1 row by 1 and subtract it from 2 row); R3 - 3 R1 → R3 (multiply 1 row by 3 and subtract it from 3 row)
1 0.5 -1 -1.5
0 2.5 0 5.5
0 2.5 2 9.5
R2 / 2.5 → R2 (divide the 2 row by 2.5)
1 0.5 -1 -1.5
0 1 0 2.2
0 2.5 2 9.5
R1 - 0.5 R2 → R1 (multiply 2 row by 0.5 and subtract it from 1 row); R3 - 2.5 R2 → R3 (multiply 2 row by 2.5 and subtract it from 3 row)
1 0 -1 -2.6
0 1 0 2.2
0 0 2 4
R3 / 2 → R3 (divide the 3 row by 2)
1 0 -1 -2.6
0 1 0 2.2
0 0 1 2
R1 + 1 R3 → R1 (multiply 3 row by 1 and add it to 1 row)
1 0 0 -0.6
0 1 0 2.2
0 0 1 2
x = -0.6
y = 2.2
z = 2
Answer:
650
Step-by-step explanation:
Answer:
7
Step-by-step explanation:
Answer:
87
Step-by-step explanation:
Look at it upside down!
The function is computed below based on the information. The answers will be:
1. -11
2. -1
<h3>How to compute the function?</h3>
f(x) = x²-11x+28
g(x) = x-4
(f+g)(-5) = (-5² - 11 × 5 + 28) + (-5 - 4)
= 25 - 55 + 28 - 9
= -11
(f-g)(5)
= = (5² - 11 × 5 + 28) + (5 - 4)
= 25 - 55 + 28 + 1
= -1
Learn more about functions on:
brainly.com/question/25638609
#SPJ1